(untitled) (Circe de clásicos y modernos, 2018)
The author of this paper reads Apologeticum by Tertullian as a text of ideological transition between the early messianic Christian writings and political fourth century theology, i.e. a work that combines Imperial theology and Christianity. Leaving apart the theological disputes with Judaism, Tertullian proposes a frontal discussion with the Romans on the relationship of the concept of divinity with political power and wants to show that theology and Christian ethics are much more appropriate for a reality as Roman Empire which has imposed the polytheistic tradition. His argumentation stands out the reciprocation between monotheism and universal monarchy.